A plurality of causal mechanisms explains the persistence or transience of soil seed banks - Sartor, Carmen Elena (2010)
Annual forbs form short-term persistent soil seed banks whereas perennial grasses form mostly transient ones in the central Monte desert. A conceptual framework predicts that annual forb seeds will have primary dormancy, whereas perennial grasses will have low dormancy levels. We assessed whether the dormancy traits of four annual forb species and five perennial grass species can account for their soil seed bank dynamics. To overcome dormancy, we treated perennial grasses and autumn annual forbs with high temperatures, and spring annual forbs with low temperatures. To force seeds into secondary dormancy we exposed non-dormant perennial grasses to low temperatures. Most of the annual forbs and two perennial grasses (Setaria leucopila and Sporobolus cryptandrus) showed low germination rates. The remaining perennial grasses presented moderate (Pappophorum caespitosum and Digitaria californica) or high germination levels (Trichloris crinita). Low temperatures increased germination in spring forbs (Chenopodium papulosum and Parthenium hysterophorus), but high temperatures did not break dormancy in autumn forbs (Sphaeralcea miniata and Phacelia artemisioides). Germination of perennial grasses increased after they had been exposed to high temperatures, but only two species reentered into dormancy under low temperature. Given that in the central Monte desert winter-autumn granivores eat mainly grass seeds, we conclude that high seed dormancy and low consumption may contribute to the persistent soil seed bank of most forbs, and that seed dormancy itself does not explain the transience of grass seed banks.